NATURAL HISTORY AND PREDICTORS OF VISION LOSS IN EYES WITH DIABETIC MACULAR EDEMA AND GOOD INITIAL VISUAL ACUITY. Issue 10 (October 2021) - Lent-Schochet, Daniella; Lo, Therlinder; Luu, Kieu-Yen; Tran, Steven; Wilson, Machelle D.; Moshiri, Ala; Park, Susanna S.; Yiu, Glenn
Abstract : Purpose: To identify clinical and anatomic factor–associated vision loss in eyes with treatment-naïve diabetic macular edema and good initial visual acuity. Methods: Retrospective cohort study after long-term history of eyes with untreated center-involving diabetic macular edema and baseline visual acuity ≥ 20/25 seen at the University of California, Davis Eye Center between March 2007 and March 2018. We collected characteristics including diabetes type, hemoglobin A1c, presence of visual symptoms, visual acuity, and diabetic retinopathy severity; and spectral-domain optical coherence tomography biomarkers including central subfield thickness, intraretinal cyst size, intraretinal hyperreflective foci, disorganization of retinal inner layers, and outer layer disruptions to determine factors associated with vision loss as defined by DRCR Protocol V as threshold for initiating aflibercept therapy. Results: Fifty-six eyes (48 patients) with untreated diabetic macular edema and mean baseline visual acuity of logMAR 0.05 ± 0.05 (Snellen 20/22) were followed for an average of 5.1 ± 3.3 years, with a median time to vision loss of 465 days (15 months). Older age (hazard ratio [HR] 1.04/year, P = 0.0195) and eyes with severe NPDR (HR 3.0, P = 0.0353) or proliferative diabetic retinopathy (HR 7.7, P = 0.0008) had a higher risk of a vision loss event. None of the spectral-domain optical coherence tomography biomarkers were associated with vision loss except central subfield thickness (HR 0.98, P = 0.0470) and cyst diameter (HR 1.0, P = 0.0094). Conclusion: In eyes with diabetic macular edema and good initial vision, those with older age and worse diabetic retinopathy severity should be monitored closely for prompt treatment initiation when vision loss occurs. Abstract : In eyes with untreated diabetic macular edema and good baseline best-corrected visual acuity, older age and worse diabetic retinopathy severity are associated with greater risk of vision loss. Patients with these risk factors should be monitored closely for prompt treatment when vision loss occurs.